HISTORICAL PERSPECTIVE OF GOVERNANCE AND POLITICS IN ISLAMIC REPUBLIC OF PAKISTAN 1947-1971 - Iqra Nazeer; Dr. Sohail Akhtar; Fazeel Ashraf Qaisrani; Muhammad Sadeeq; Khursheed Begum; Dilshad Noor (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
The paper is primarily dealing with the governance and politics in Pakistan after its emergence in 1947. Quaid-e-Azam Muhammad Ali Jinnah tried his best to set up a good governance system in the country as a founding father. Muslim League as dominant political party formed its government but different conspiracies and involvement of undemocratic forces affected the governance and politics during this era. Non-elected behaviour created un rest in the country and due to the behavior of the political leaders, Ayub take over, his political and administrative strategies, 1st Martial Law put its influence on politics not only but the EBDO also destabilized democracy in Pakistan. This paper is an attempt to high light the governance and politics of Pakistan 1947-1971 how political leadership and military intervene influenced on governance and politics.